Dopamine D(4) Receptors Regulate GABA(A) Receptor Trafficking via an Actin/Cofilin/Myosin-dependent Mechanism - Graziane, Nicholas M. (American Society for Biochemistry and Molecular Biology, 2009)
The GABA(A) receptor-mediated inhibitory transmission in prefrontal cortex (PFC) is implicated in cognitive processes such as working memory. Our previous study has found that GABA(A)R current is subject to the regulation of dopamine D(4) receptors, a PFC-enriched neuromodulator critically involved in various mental disorders associated with PFC dysfunction. In this study, we have investigated the cellular mechanism underlying D(4) modulation of GABA(A)Rs. We found that the density of surface clusters of GABA(A)R β2/3 subunits was reduced by D(4), suggesting that the D(4) reduction of GABA(A)R current is associated with a decrease in functional GABA(A)Rs at the plasma membrane. Moreover, the D(4) reduction of GABA(A)R current was blocked by the actin stabilizer phalloidin and was occluded by the actin destabilizer latrunculin, suggesting that D(4) regulates GABA(A)R trafficking via an actin-dependent mechanism. Cofilin, a major actin depolymerizing factor whose activity is strongly increased by dephosphorylation at Ser(3), provides the possible link between D(4) signaling and the actin dynamics. Because myosin motor proteins are important for the transport of vesicles along actin filaments, we also tested the potential involvement of myosin in D(4) regulation of GABA(A)R trafficking. We found that dialysis with a myosin peptide, which competes with endogenous myosin proteins for actin-binding sites, prevented the D(4) reduction of GABA(A)R current. These results suggest that D(4) receptor activation increases cofilin activity presumably via its dephosphorylation, resulting in actin depolymerization, thus causing a decrease in the myosin-based transport of GABA(A)R clusters to the surface.